The role of genetics in adaptation of agriculture to climate change - Tuberosa, Roberto (Henry Stewart Talks, 2014)
Strategies to mitigate the impact of climate change on crops, Phenotyping and genotyping for climate resilient crops, Genomics approaches and strategies, Chasing QTLs for drought resistance in wheat and maize, Genomics-assisted breeding for enhancing resistance to abiotic stress, Perspectives and future challenges